Analisis Ijarah Muntahiyah Bit Tamlik dalam Perspektif Hukum Islam dan Hukum Positif Indonesia - Muhammad Romi; Aslati Aslati; Mawardi Dalimunthe (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This research aims to analyze the law of Ijarah Muntahiyah Bit Tamlik (IMBT) in the perspective of Islamic law and positive law in Indonesia, as well as examine the suitability and synergy between the two. IMBT is a complex form of Islamic financing contract because it combines two different contracts, namely rent (ijarah) and transfer of ownership (grant or sale). This research uses a normative juridical method with a comparative approach and critical analysis, namely comparing the legal basis of IMBT in muamalah fiqh and legislative regulations in Indonesia, including the Compilation of Sharia Economic Law, Banking Law, Bank Indonesia Regulations, and Civil Code. Data collection techniques are carried out through library research by examining primary and secondary sources. The results of the study show that Islamic law allows IMBT contracts to be safe if the lease contract and the promise of ownership are separated and not made in one binding contract. Transfer of ownership can only be done after the lease period ends, and the contract structure must be in accordance with the principles of justice, clarity, and free from elements of usury and gharar. In positive law in Indonesia, IMBT is also legally recognized, although it has not been regulated in a special law. However, its existence has been legitimized through the DSN-MUI fatwa, the Compilation of Sharia Economic Law (KHES), the Sharia Banking Law, and Bank Indonesia Regulations. There is substantial synergy between the principles of fiqh muamalah and positive law in Indonesia, although there is still a need to strengthen regulations and epistemological reconstruction so that IMBT can be carried out more comprehensively, legally according to sharia, and strong in national law in modern economic practices.